SUPERVISI PENDIDIKAN IPA BERCIRIKAN DIALOG PROFESIONAL KESEJAWATAN DALAM KONTEKS PELAKSANAAN MBS - Wiyanto, - (Universitas Negeri Semarang, 2007)
Stakeholders have high expectation on natural sciences education to makestudents ready to compete in the fast changing world. To meet the expectation, thenatural sciences education needs an educational supervision to assure its quality. Thearticle will discuss a model characterized by professional collegial dialogues. It meansthat the dialogues must be democratic, equal and respecting each other according totheir position. This model has an important role in the school-based management. Thediscussion includes the rational, the assumption, the goals, the modelÃ¢â¬â¢s components andtheir relationship, the implementation strategy, and the parameter of success.Kata kunci: supervisi pendidikan, IPA, dialog profesional kesejawatan